Sterile Subdural Empyema Secondary to Submandibular Abscess: A Case Report - Khansa, Amany; Geraldi, Iskandar Purba; Fadli, Nurul (Acta Neurologica Indonesia, 2025)
Introduction: Subdural empyema is a rare, serious condition characterized by the accumulation of pus in the space between the dura mater and the arachnoid mater. One of the rare causes is odontogenic infection. This case report discusses a sterile subdural empyema as a complication of a submandibular abscess. Case: A 46-year-old man presented with loss of consciousness, seizure, fever, and swelling of the right lower jaw. Three months earlier, he had undergone an extraction of his lower right tooth. A CT scan of the patient's head showed a crescent-shaped hypodense lesion in the right parietotemporooccipital region and a hypodense lesion with an enhancing edge in the submandibular area. A buccal incision and drainage procedure and craniotomy were performed. Pus was found in the subdural space. Cultures were taken from blood and both drainage sites, but culture did not show any growth of microorganisms. Meropenem and metronidazole were used as antibiotics. The patient later died due to multiple organ dysfunction syndrome (MODS). Discussion: Subdural empyema is an infectious condition caused by hematogenous spread, direct spread of surrounding tissue, and venous or lymphatic spread. One rare cause is odontogenic infection. The main treatment includes surgical intervention and antibiotic therapy. Infection is generally polymicrobial. Previous antibiotic administration or inappropriate culture medium can cause negative culture. Conclusion: Subdural empyema can arise from odontogenic infection. Therefore, rapid and appropriate identification and treatment are essential to prevent intracranial complications and reduce mortality and morbidity. Keywords: subdural empyema; odontogenic infection complications; intracranial infection